A Study of Heart Disease Patients by Using Log-Linear Models: A Case Study of the Paolo Memorial Samutprakarn Hospital - รักตะเมธากูล ผู้ช่วยศาสตราจารย์ ดร.สิทธิพงศ์; ยิ้มประยูร ผู้ช่วยศาสตราจารย์ ดร.พรพิศ (Journal of Food Health and Bioenvironmental Science, 2016)
Heart disease is a noninfectious disease which is on the increase throughout the world and has become a serious problem for public health in many countries. The main objective of this study was to test the relationship between personal and heart disease variables by using log-linear models. In this study, the data sets were the number of heart disease patients who were admitted between January thru December 2012 at the Paolo Memorial Hospital. Test of independence between any two variables used the chi-square tested and Cramer’s V. In addition, two-dimensional log-linear models were used to obtain estimated parameters of maximal models which are the best model for this study.